Keefektifan Model Problem Based Learning Berbantu Media Audio-Visual Terhadap Peningkatan Kemampuan Penalaran Siswa - Citra Dwi Pitaloka; Bagus Ardi Saputro; Fine Reffiane (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2021)
The purpose of this research is to find out how the Effectiveness of Problem Based Learning Learning Model on Improving the Reasoning Ability of Class II Students in terms of fractional materials assisted by audio-visual media. The research design used in this study was the One Group Pretest Posttest Design. From the pretest value the average value of the class is 57.88 while the posttest value is 86.83, and based on the t-test analysis obtained tcount (34.449) t table (2.062) so H0 is rejected, meaning that the average before and after being treated is not same. Also shown in the classical mastery test, the results of the pretest reached 27% classical learning completeness. The results of the posttest achieved a learning completeness of 88%. A class is said to be complete if there are 67% of students who have completed learning. Thus, the posttest results can be said to be classically complete with 88% of students completing learning. It can be concluded that the Problem Based Learning learning model assisted by Audio-Visual Media is effective in increasing the reasoning abilities of second grade students at SD Negeri Pleburan 02 Semarang.